2012
DOI: 10.1176/appi.ps.201100473
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping Prescriptions of Stimulants for Children and Adolescents With Attention-Deficit Hyperactivity Disorder

Abstract: In an effort to improve the quality and safety of prescription of controlled substances in younger populations, interventions or policies should be devised to target both the service providers and the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Different methods have previously been used to identify deviant patterns of drug use with data from prescription databases, [14][15][16][17][18][19][20][21][22][23][24] such as individuals visiting multiple prescribers and/or multiple pharmacies (doctor/pharmacy shopping), high levels of dispensed drugs and simultaneous dispensings of drugs with a known abuse potential. 21 Some may be used as proxy measures of medical misuse of prescription drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have previously been used to identify deviant patterns of drug use with data from prescription databases, [14][15][16][17][18][19][20][21][22][23][24] such as individuals visiting multiple prescribers and/or multiple pharmacies (doctor/pharmacy shopping), high levels of dispensed drugs and simultaneous dispensings of drugs with a known abuse potential. 21 Some may be used as proxy measures of medical misuse of prescription drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the treatment gap (i.e., drug holiday) and combination therapy were not analyzed in this study [ 49 ]. Furthermore, a number of patients who switch from IR–MPH to OROS–MPH or ATX may eventually change their drug therapy back to IR–MPH [ 50 ]. These particular patient groups were not separately analyzed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, paediatric populations constitute a small percentage of the subjects analysed, for example, 7.4% in the study on opioid use by Cepeda et al, 15 19.1% in the study by Lin et al 21 on the use of primary health resources, and 28.5% in the study on upper respiratory infections by Wang et al 23 Only three studies exclusively reported on children, investigating ADHD, fever, and emergency visits. 16,19,22 Another factor that has to be considered as a limitation is the heterogeneity in defining doctor-shopping phenomenon and the formats of its prevalence. The heterogeneity in data presentation hindered comparisons between studies as well.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 4 (36.4%) out of 11 studies analysed the use of controlled substances such as opioids and stimulants. [15][16][17][18] Another six (54.5%) studies focused on the use of health care facilities either in general or in terms of a specific complaint such as a fever and respiratory infection and the need for an emergency consultation, [19][20][21][22][23][24] while one of the papers analysed doctor shopping as a form of child abuse. 14…”
Section: Specialities Covered By Doctor-shopping Studiesmentioning
confidence: 99%
See 1 more Smart Citation